Determination of the Vegetative Phase Critical for Monitoring Wheat Nitrogen Status Tropical Through Digital Color Analysis and Index Camera Reflectance - Charlotte Putri Bandono; Bistok Hasiholan Simanjuntak (Westscience Press, 2026)
Reliable nitrogen (N) monitoring remains a major challenge in tropical wheat systems due to dynamic N uptake, redistribution, and environmental variability across growth stages. Although RGB based digital imaging offers a rapid and non-destructive alternative, its accuracy is often limited by the phase-dependent relationship between leaf color and nitrogen status. This study aimed to identify the critical vegetative stage that provides the most reliable estimation of leaf nitrogen in tropical wheat (Triticum aestivum L.). A greenhouse experiment was conducted using a randomized block design with five nitrogen rates (0–300 kg urea ha⁻¹). Leaf images were collected at four vegetative stages (V1–V4), and RGB values were transformed into vegetation indices (ExG, GLI, TGI, and NGRDI). These indices were correlated with chlorophyll and leaf nitrogen content using Pearson analysis. Results showed a clear phase-specific pattern, with the strongest relationship observed at V3 (second node emergence). The ExG index exhibited a very strong and significant correlation with leaf nitrogen (r = 0.97; p < 0.01). In contrast, weak correlations at V1 and negative trends at V4 were associated with limited nitrogen accumulation and remobilization processes.These findings highlight V3 as the optimal stage for nitrogen estimation and emphasize the importance of a phase-specific approach to improve RGB based monitoring in tropical wheat systems.